Design to Improve Player On-Boarding and Decision-Making Processes in Video Games: A Systematic Review. (September 2018) - Endresen, Ian; Nathan-Roberts, Dan
Decision-making performance in video games play a vital role in player success and frustration. As video games become more complex, designers will need to develop appropriate methods to assist players to address the increased learning requirements. To understand current research on player decisions and behaviors, a systematic review was performed, identifying 202 articles and fully analyzing a total of 14 studies. After the analysis of all studies, it was determined that efficient on-boarding and decision-making design strategies requires a multi-disciplinary approach. Future research should bridge the gap of independent disciplines into a cohesive methodology for effective video game design.